VAN ANDEL, Tjeerd H.; RUNNELS, C. Beyond the Acropolis: A Rural Greek Past. California: Stanford University Press, 1987. 221p. - Chevitarese, André Leonardo (Classica - Revista Brasileira de Estudos Clássicos, 1993)
VAN ANDEL, Tjeerd H.; RUNNELS, C. Beyond the Acropolis: A Rural Greek Past. California: Stanford University Press, 1987. 221p.